Evaluation of healthcare provider motivation in the Kenge Health Zone, Democratic Republic of Congo, within the framework of performance-based financing - Idiamwana, Blaise K.; Miyalu, Junior K.; Mpunga, Dieudonné M. (Orapuh Journal, 2026)
IntroductionPerformance-based financing is one mechanism for improving the motivation of healthcare providers. To date, there is limited evidence on its effects on the motivation of healthcare staff in the Kenge Health Zone five years after project implementation.PurposeThis study aimed to describe the motivating factors among healthcare providers in the Kenge Health Zone, a beneficiary of performance-based financing (PBF).MethodsA descriptive cross-sectional study was conducted from 6 to 26 March 2024 among 302 healthcare providers selected through proportional sampling. Using SPSS version 25 and a 22-item Likert-scale questionnaire with five response options coded from 1 to 5, internal consistency was assessed using Cronbach’s alpha coefficient (0.736). The level of motivation was determined by comparing each respondent’s mean score with the overall mean of the scale, allowing classification of providers according to motivation level.ResultsSatisfaction with hygiene conditions (61.9%) and management (80.8%) was high, whereas perceived salary satisfaction was low (37.4%). Approximately two-thirds of participants had not received recent continuing professional education. The mean motivation score was 3.76. Slightly more than half of the healthcare providers (57.3%) were classified as motivated. The proportion of motivated women was slightly higher than that of motivated men.ConclusionThe performance-based financing programme appears to have a positive effect on certain aspects of healthcare worker motivation; however, challenges related to remuneration and professional development persist. Staff motivation remains a concern for health authorities and is influenced by multiple factors. Further studies incorporating a broader range of motivational determinants are recommended to enable large-scale evaluation.